Perancangan Sistem Informasi Pengolahan Nilai Berbasis Web Pada MTs Al Ghazaly Bogor - Sefrika Sefrika; Helina Apriyani; Enok Tuti Alawiah (Jurnal Mantik Penusa, 2017)
MTs Al Ghazaly Bogor is a junior high school education institution located in Bogor City. To manage academic values, the school has been using manual methods and has no information system. As a result, value-processing processes often experience obstacles, especially for absent recap process, value inputs from study teachers, value-processing by classmates and reporting to principals. One way that can be done is to design a web-based academic value processing information system that will help teachers improve their performance. This research aims to design a web based academic value processing information system that will be implemented at MTs Al Ghazaly Bogor. Software system development is made using the waterfall method. The results of the study can be used to help teachers' performance and facilitate students access the academic final report based on the website.